1997
DOI: 10.1038/nsb0597-374
|View full text |Cite
|
Sign up to set email alerts
|

Structure of human IgM rheumatoid factor Fab bound to its autoantigen IgG Fc reveals a novel topology of antibody—antigen interaction

Abstract: Rheumatoid factors are the characteristic autoantibodies of rheumatoid arthritis, which bind to the Fc regions of IgG molecules. Here we report the crystal structure of the Fab fragment of a patient-derived IgM rheumatoid factor (RF-AN) complexed with human IgG4 Fc, at 3.2 A resolution. This is the first structure of an autoantibody-autoantigen complex. The epitope recognised in IgG Fc includes the C gamma 2/C gamma 3 cleft region, and overlaps the binding sites of bacterial Fc-binding proteins. The antibody r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
135
1

Year Published

1999
1999
2012
2012

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 210 publications
(144 citation statements)
references
References 37 publications
8
135
1
Order By: Relevance
“…The region of Sm D3 that is involved in binding to Sm BЈ in vivo consists primarily of aa [21][22][23]39, and 69 -75 of D3 (5). Interestingly, D3-positive patients make high levels of autoantibodies against aa 60 -68 and 76 -106, surrounding but conspicuously avoiding one of the major regions (aa 69 -75) involved in direct intermolecular bonding to Sm BЈ in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…The region of Sm D3 that is involved in binding to Sm BЈ in vivo consists primarily of aa [21][22][23]39, and 69 -75 of D3 (5). Interestingly, D3-positive patients make high levels of autoantibodies against aa 60 -68 and 76 -106, surrounding but conspicuously avoiding one of the major regions (aa 69 -75) involved in direct intermolecular bonding to Sm BЈ in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…No evidence of any malignant lymphoproliferative disorder was disclosed by physical examination, thorax-and abdomen-computed tomography or by bone marrow biopsy in the remaining cases. Seven HCVnegative patients with MC syndrome were selected as negative controls (patients [18][19][20][21][22][23][24]. Mixed cryoglobulinemia syndrome was associated with Sjogren's syndrome in three cases (patients [20][21][22], with chronic hepatitis B virus infection (HBs Ag and HBV DNA-positive in serum) in patient 18 and undifferentiated connective tissue disease in patient 23.…”
Section: Patientsmentioning
confidence: 99%
“…The plates were then washed and incubated with a horseradish peroxidase-labeled goat anti-human IgM (Sigma-chemical Laboratories, St Louis, MO, USA). As negative control, the assays were performed with IgM purified from patients with cryoglobulinemia but HCV seronegative (patients [18][19][20][21][22][23][24]. Positive controls consisted of mouse monoclonal antibodies specific for HCV antigens (IBT-Immunological and Biochemical Testsystems GmbH-Germany, and Novocastra, Benton lane, Newcastle upon Tyne UK).…”
Section: Binding Of Hepatitis C Virus Antigensmentioning
confidence: 99%
“…Several autoantibodies are produced in conjunction with manifestations of RA (Goldbach-Mansky et al 2000). Rheumatoid factors are the characteristic autoantibodies, binding to the Fc region of agalactosylated IgG (IgG 0 ) molecules (Carson et al 1987;Corper et al 1997) and found in elevated levels in the sera of RA patients. IgG 0 has been directly implicated in the pathogenesis of RA (Bond et al 1996).…”
Section: Introductionmentioning
confidence: 99%